2012
DOI: 10.1111/j.1469-0691.2012.03884.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bacterial load, morbidity and cagA gene in patients infected by Helicobacter pylori

Abstract: One hundred and seventy-six biopsies of the gastric corpus and antrum from 97 patients were processed using classical and molecular methods in order to study the relationship between the factor cagA of Helicobacter pylori, bacterial load and morbidity. Bacterial load in patients with cagA was greater than in patients without it, both in the antrum and corpus (p<0.01). There was a statistically significant association between cagA and consumption of proton pump inhibitors (adjusted odds ratio 3.11). Haemorrhage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…This information has been associated with disease eradication rate, ulcer healing rate, and antral inflammation (15). In addition, our previously reported results showed that upper gastrointestinal bleeding was more closely associated with the bacterial load than the presence of the cagA gene, suggesting the importance of quantifying the bacterial load in order to gain a better understanding of the complex interaction between the microorganism and gastric mucosa (1).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This information has been associated with disease eradication rate, ulcer healing rate, and antral inflammation (15). In addition, our previously reported results showed that upper gastrointestinal bleeding was more closely associated with the bacterial load than the presence of the cagA gene, suggesting the importance of quantifying the bacterial load in order to gain a better understanding of the complex interaction between the microorganism and gastric mucosa (1).…”
Section: Discussionmentioning
confidence: 94%
“…The microorganisms were detected using a specific control probe marked with a different fluorochrome (VIC) (see Fig. S1 in the supplemental material) (1). The reaction took place in a real-time PCR 7500 apparatus (Applied Biosystems).…”
Section: Methodsmentioning
confidence: 99%
“…We observed a two log range of H. pylori loads in the stool and the load is significantly higher in those with a cagA -positive strain. Density of H. pylori in the stomach also varies among infected individuals, and a higher H. pylori load in the stomach among individuals infected with a cagA -positive strain has been previously reported [41]. The relationship between H. pylori load in the stool and density of infection in the stomach, as well as other possible factors such as level of inflammation, disease state, or bacterial genetic factors, is not presently understood.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies report that the presence of a factor increases the density of a microbe in experimental hosts, as determined by colony counts for various body sites (Belda et al, 2012;Crotty Alexander et al, 2010;Kasper et al, 2014), that is, they identify proliferation factors. Stp1 is a malevolence factor in that system.…”
Section: Specific Molecular Factorsmentioning
confidence: 99%